2017
DOI: 10.1007/s00253-017-8390-6
|View full text |Cite
|
Sign up to set email alerts
|

Application of the entomogenous fungus, Metarhizium anisopliae, for leafroller (Cnaphalocrocis medinalis) control and its effect on rice phyllosphere microbial diversity

Abstract: Microbial pesticides form critical components of integrated pest management (IPM) practices. Little, however, is known regarding the impacts of these organisms on the indigenous microbial community. We show that Metarhizium anisopliae strain CQMa421 was highly effective in controlling the rice leafroller, Cnaphalocrocis medinalis Guenee. In addition, M. anisopliae distribution and its effects on phyllosphere microbial diversity after application in field trials were investigated. Phylloplane specific distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 78 publications
3
20
1
Order By: Relevance
“…Given that a significant decline in all detectable Beauveria was observed by 30 DAI using PCR, this was not unexpected but may indicate that initial inocula levels did not have a lasting effect. A recent study by Hong et al (2017) also demonstrated that an application of M. anisopliae had a minimal impact on the endogenous microbial diversity of rice plants within the phyllosphere, with only transient changes in bacterial abundance/diversity that may have resulted in some small benefits to the plant. Thus multitrophic interactions are important to consider, in addition to any possible ecosystem impacts that may influence performance of a biocontrol agent applied to agroecosystems ( Ownley et al, 2010 ).…”
Section: Discussionmentioning
confidence: 97%
“…Given that a significant decline in all detectable Beauveria was observed by 30 DAI using PCR, this was not unexpected but may indicate that initial inocula levels did not have a lasting effect. A recent study by Hong et al (2017) also demonstrated that an application of M. anisopliae had a minimal impact on the endogenous microbial diversity of rice plants within the phyllosphere, with only transient changes in bacterial abundance/diversity that may have resulted in some small benefits to the plant. Thus multitrophic interactions are important to consider, in addition to any possible ecosystem impacts that may influence performance of a biocontrol agent applied to agroecosystems ( Ownley et al, 2010 ).…”
Section: Discussionmentioning
confidence: 97%
“…Conidial yield, stress tolerances, and virulence are very important parameters for entomopathogenic fungi with respect to biological control applications of the fungus [5052]. Previous works in other filamentous fungi have shown that chitin synthesis impacts fungal conidiation.…”
Section: Discussionmentioning
confidence: 99%
“…Use of Metarhizium anisopliae (Metschn.) has been shown to be effective against the rice leafroller ( Cnaphalocrocis medinalis Güenée, Lepidoptera: Crambidae), without adversely affecting the rice phyllosphere microbial diversity, 26 and the effect of the insect microbiota in mediating susceptibility to infection is being increasingly examined 27,28 …”
Section: Introductionmentioning
confidence: 99%
“…25 Use of Metarhizium anisopliae (Metschn.) has been shown to be effective against the rice leafroller (Cnaphalocrocis medinalis Güenée, Lepidoptera: Crambidae), without adversely affecting the rice phyllosphere microbial diversity, 26 and the effect of the insect microbiota in mediating susceptibility to infection is being increasingly examined. 27,28 However, additional information is needed concerning the use of entomopathogenic fungi as components of sustainable pest control strategies for the control of N. lugens on rice.…”
Section: Introductionmentioning
confidence: 99%